An Analytical Solution to the Electromagnetic Performance of an Ultra-High-Speed PM Motor. (12th September 2019) - Cheng, Wenjie; Deng, Zhikai; Xiao, Ling; Zhong, Bin; Sun, Yanhua
Abstract : Bipolar rotors with cylindrical permanent magnets (PMs), which are magnetized in parallel, are generally used in ultra-high-speed permanent magnet synchronous motors (PMSMs). Aiming for this type of PMSM, two methods, namely, the Poynting theorem and the Maxwell stress tensor, were used to deduce the analytic expression of the electromagnetic driving torque. A locked-rotor simulation by the finite element (FE) method verifies the analytical solution. In addition, the cogging torque, back-electromotive force (emf), armature reaction inductance, etc., were calculated, compared, and discussed. The no-load back-emf was checked by a 60, 000 rpm free coast experiment. The proposed analytical solution is very convenient to guide the design of the ultra-high-speed PMSM and check its performance.